What is hidden behind persistent Inferior vena cava thrombosis? - João M. Cabral; Daniel Mendes; Carlos Pereira; Ivone Silva; Rui Machado (Angiologia e Cirurgia Vascular)
BACKGROUND: Primary tumors of the inferior vena cava (IVC) are rare. They most commonly arise from the smooth muscle of the IVC walls, known as leiomyomas.